The Evolution of Curriculum Evaluation Research in Schools: A Systematic Literature Review - Niam Wahzudik (Proceedings of International Conference on Science, Education, and Technology, 2026)
Curriculum evaluation plays a pivotal role in educational quality improvement and evidence-informed decision-making in schools. Nevertheless, research in this field remains fragmented across diverse evaluation models, methodological approaches, and educational contexts, limiting a comprehensive understanding of its development. This study systematically examines the evolution of school-based curriculum evaluation research by identifying publication trends, dominant evaluation models, methodological developments, paradigm shifts, major and emerging themes, research gaps, and future directions. A systematic literature review was conducted following the PRISMA 2020 framework. Studies published between 2016 and 2026 were retrieved from Google Scholar. Of the 200 initially identified records, 44 journal articles and conference papers met the inclusion criteria after duplicate removal, title and abstract screening, full-text assessment, and document authentication. The data were analysed using descriptive analysis, VOSviewer-assisted bibliometric mapping, and thematic synthesis. The findings indicate a substantial increase in publications between 2022 and 2026. The CIPP model was the most frequently identified evaluation framework, while descriptive studies, single-case designs, and document analyses remained methodologically prevalent. Major themes included curriculum implementation and effectiveness, evaluation models, inclusive education, and the conceptual development of curriculum evaluation. The field has gradually shifted from objective- and outcome-oriented evaluation towards more contextual, adaptive, participatory, and governance-oriented perspectives. However, multisite, longitudinal, comparative, and participatory studies, as well as technology-supported evaluation, remain limited. Future research should develop adaptive, data-informed, participatory evaluation models that are embedded in school governance and decision-making systems.